José Ferrater Mora, Unamuno, bosquejo de una filosofía. Editorial Sudamericana, Buenos Aires, 1957; 141 pp. - Earle, Peter G. (El Colegio de México, 1962)
Se reseñó el libro: Unamuno, bosquejo de una filosofía.